Sepsis in Abdominal Surgery in the Intensive Care Unit - Khaitov Dilshod Khayotovich; Djuraev Ikhtiyor Bozorovic (Genius Journals, 2023)
The cause of a systemic inflammatory reaction may be lesions of various organs: distal esophagus, stomach, duodenum, bile ducts, various parts of the small and large intestine, appendix, liver, spleen, pancreas (including parapancreatic abscesses and infected pseudocysts of the gland), as well as inflammatory diseases of the pelvic organs in women. To date, it is known that the severity of the systemic inflammatory reaction in secondary peritonitis determines the severity of the patient's condition and prognosis. Thus, a promising scientific study is to assess the significance of biomarkers of inflammation in order to control the effectiveness of therapeutic measures and predict possible outcomes of the disease at the early stages of hospitalization
Keywords: sepsis; biomarkers of inflammation; complex treatment; abdominal surgery